Penyuluhan Otitis Media Akut kepada Anak Panti Asuhan Advent Peduli - Sembiring, Budi Darmanta; Anto, Endy Juli; Fauzi, Tengku Muhammad; Siahaan, Jekson Martiar; Tarigan, Menang Bastanta; Sijabat, Kesia; Sihaloho, Kerin Repaskatri; Manik, Widya Dayanti Feronika; Simanjuntak, Jeremia; Wijaya, Mega; Sihaloho, Lovian Nauli; Sembiring, Mikael; Panjaitan, Bintang Andika; Sitompul, Michael Sabatino; Momot, Estela Salomina (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
In accordance with the application of the Tri Darma of Higher Education in the doctor's professional study program, one of which is community service. The purpose of community service activities is to provide explanations and education that can influence community behavior. This community service was carried out at an advent orphanage caring for children and adolescents with 25 participants. This community service activity was carried out on December 6, 2023, with the material of acute otitis media. This topic is very much needed in order to provide information and knowledge about acute Otitis media. Behavior to maintain ear hygiene and health to prevent this disease. Lack of knowledge many are subjected to unfavorable issues. Through this health counseling, it is expected that children and adolescents at Advent Peduli Orphanage, Gg. Kasih no 8, Sudirejo II, Kec. Medan Kota are always motivated to stay alert when playing with friends and keep their ears healthy.